2011
DOI: 10.1093/icesjms/fsr076
|View full text |Cite
|
Sign up to set email alerts
|

Using qualitative and quantitative stakeholder knowledge: examples from European deep-water fisheries

Abstract: Lorance, P., Agnarsson, S., Damalas, D., des Clers, S., Figueiredo, I., Gil, J., and Trenkel, V. M. 2011. Using qualitative and quantitative stakeholder knowledge: examples from European deep-water fisheries. – ICES Journal of Marine Science, 68: 1815–1824. Stakeholder knowledge was collected through questionnaires and cognitive maps and used to summarize biological, environmental, technical, management, and socio-economic factors for several deep-water fisheries, identifying regional management issues and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…This means that management strategies start from a low level of knowledge (Clark, 2009) and scientific assessment usually begins some years after a commercial fishery has been established and in conditions where the resource is already overfished or has collapsed (Haedrich et al, 2001;Priede et al, 2011). Also, deep-sea fisheries are generally data-poor, and many deepwater species are also difficult to age reliably (Lorance et al, 2011). Ye et al (2011) point out that to overcome the data limitation and absence of modelling support, simple indicators have to be used to assess the current state and monitor changes of the fishery and its ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…This means that management strategies start from a low level of knowledge (Clark, 2009) and scientific assessment usually begins some years after a commercial fishery has been established and in conditions where the resource is already overfished or has collapsed (Haedrich et al, 2001;Priede et al, 2011). Also, deep-sea fisheries are generally data-poor, and many deepwater species are also difficult to age reliably (Lorance et al, 2011). Ye et al (2011) point out that to overcome the data limitation and absence of modelling support, simple indicators have to be used to assess the current state and monitor changes of the fishery and its ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a pragmatic approach which involves nature of both qualitative and quantitative data, similar to; Ahmed et al (2013), Mollinga and Gondhalekar (2012), Lorance et al (2011), andLoucks et al (2005). Hence a hybrid-approach of qualitative and quantitative methodology was employed in this study for better presentation and understanding of the results.…”
Section: Methodsmentioning
confidence: 99%
“…This paper revealed that the majority of stakeholders in the study area did not have much knowledge on the reformed water governance institutions, an element that put pressure on policy makers to follow more participatory approaches. In the study of Lorance [19], stakeholders' knowledge was collected through questionnaires in order to identify regional management issues and solutions for several deep-water fisheries. This case study demonstrated how stakeholder involvement and the use of qualitative and quantitative data both improved management processes and fish stock assessments, when data are limited.…”
Section: Expert and Stakeholder Opinions: The Scientific Basismentioning
confidence: 99%